Turkish mobile speech discrimination in real noise 4-word sentence test findings in individuals with hearing loss aged 8–12 years - Rukiye Tanisir Disci; Ozlem Konukseven (The Egyptian Journal of Otolaryngology)
Abstract Background In daily life, there has been a need to establish verbal communication with sentences instead of single-syllable words and to be tested with sentences that better reflect social life. In this study, it was aimed to evaluate signal noise ratio thresholds and speech comprehension scores in noise in children with severe sensorineural hearing loss by using real ambient noises, four-word spectral balanced sentences, and light, medium, and high input signal levels. Results A total of 40 children, including 20 children with severe sensorineural hearing loss, using bilateral hearing aids, (10.23 ± 1.64) and 20 children with normal hearing (9.25 ± 1.48), aged 8–12 years, were included in the study. The newly developed Turkish Mobile Sentence Test for Distinguish Speech in Real Noises was applied to the participants. This test is performed using spectral and coherence balanced 4-word sentences, at − 10 dB, − 5 dB, 0 dB, 5 dB, and 10 dB SNR thresholds and 40, 60, and 80 dB sound levels at shopping mall and amusement park. Children with hearing loss had higher signal noise ratio thresholds at all sound levels in shopping malls, amusement parks, and classroom environments, and their speech comprehension scores in noise were lower at these thresholds (p < 0.05). Conclusions Children with hearing loss aged 8–12 have difficulties in verbal communication, in real ambient noises, and in speech discrimination tests, even with 4-word sentences at mild, medium, and high levels of intensity, compared to children with normal hearing. Further studies evaluating hearing aid fitting settings with signal noise ratio thresholds are needed.